The Saudi National Transformation Plan and the Role of Saudi Women | خطة التحول الوطني السعودي ودور المرأة السعودية - Al Saud | آل سعود, Reema bint Bandar | ريما بنت بندر (Publishing and Public Relation Department | إدارة النشر والعلاقات العامة, 2024)
Princess Reema Bandar Al Saud, Princess Haifa bint Mohammed Al Saud, and Shaihana Al Azzaz tell the story of the empowerment of women in Saudi Arabia in episode 15 of the MBC program Wa’d (promise), which aired on April 16, 2022. | الأميرة ريما بندر آل سعود والأميرة هيفاء بنت محمد آل سعود وشيهانة العزاز يروون قصة تمكين المرأة في السعودية في الحلقة 15 من برنامج وعد (وعد) على قناة MBC والتي تم بثها في 16 أبريل 2022.